The expression of ADAMTS13 in human microvascular endothelial cells. Issue 4 (June 2016) - Wang, Anyou; Duan, Qiaohong; Wu, Jingsheng; Liu, Xin; Sun, Zimin
Abstract : ADAMTS13, as a specific von Willebrand factor (VWF)-cleaving protease, prevents microvascular thrombosis of VWF/platelet thrombi. It has been reported that human vascular endothelial cells could also synthesize and secrete ADAMTS13, and these reports were focused in human umbilical vascular endothelial cells. Considering the particularity of its huge quantity and structure of human microvascular endothelial cells (HMECs) in the body, whether ADAMTS13 is expressed in HMECs also needs to be confirmed. To investigate whether ADAMTS13 is expressed in HMECs. Real-time PCR (RT-PCR) amplification detected ADAMTS13 mRNA in HMEC-1 cell line. The expression and distribution of ADAMTS13 protein and VWF were detected by fluorescence immunoassay and western blot. We observed the expression and distribution of ADAMTS13 in HMECs. We confirmed the expression of ADAMTS13 mRNA in HMEC-1, and found that there were some partly common distributions of ADAMTS13 protein and VWF. This study provides the evidence that HMECs also express ADAMTS13. HMECs might also be a primary source for human plasma ADAMTS13. The overlap region for the distribution of ADAMTS13 and VWF suggests that ADAMTS13 might have a potential regulation role for VWF inside cells.